Prior pathology in the basal forebrain cholinergic system predisposes to inflammation-induced working memory deficits: reconciling inflammatory and cholinergic hypotheses of delirium. - CUNNINGHAM, COLM (My University, 2012)
Delirium is a profound, acute confusional state that leads to long-term cognitive decline. Increased anticholinergic medications and prior dementia, in which basal forebrain cholinergic degeneration is a prominent feature, both predict delirium. Thus, cholinergic hypoactivity is thought to be important in cognitive dysfunction during delirium, and acute systemic inflammation is a major trigger for this dysfunction. Here, we hypothesize that decreased cholinergic function confers increased susceptibility to acute inflammation-induced cognitive deficits. We used the murine-p75-saporin immunotoxin (mu-p75-sap) to induce selective lesions of the basal forebrain cholinergic system in mice, mimicking early dementia-associated cholinergic loss, and superimposed systemic inflammation using low-dose bacterial lipopolysaccharide (LPS). Intracerebroventricular injection of mu-p75-sap produced depletion of cholinergic neurons in the basal forebrain and decreased innervation of the hippocampus, but left performance on hippocampal-dependent reference and working memory tasks relatively intact. However, systemic LPS (100 μg/kg) induced acute and transient working memory deficits in lesioned animals without effect in unlesioned controls. CNS inflammatory responses were similar in normal and lesioned animals and the acetylcholinesterase inhibitor, donepezil (1 mg/kg), protected against the acute cognitive deficits in this cholinergic-dependent task. Thus, cholinergic depletion predisposes to development of acute cognitive deficits upon subsequent systemic inflammatory insult. These data provide a useful model for examining interactions between acute systemic inflammation and chronic cholinergic hypofunction in delirium and have implications for the recent trial of rivastigmine in sepsis-associated delirium.
PUBLISHED
Keywords: Delerium; Ageing; Immunology, Inflammation & Infection; Neuroscience